Extraperitoneal tissue retraction technique: An effective assistant of extraperitoneal pure single-port robotic-assisted radical prostatectomy with the da Vinci Si surgical system - Ju, Guanqun; Wang, Zhijun; Shi, Jiazi; Xu, Weidong; Zhang, Zongqin; Yin, Lei; Xu, Dongliang; Ren, Shancheng (Frontiers in Surgery, 2022)
Objective The limitations of tissue retraction and the amount of surgical working space have a great impact on extraperitoneal single-port robotic-assisted radical prostatectomy (sp-RARP) with the multiport robotic surgical system. We used an extraperitoneal tissue retraction technique to achieve tissue exposure and working space expansion. This study evaluated the safety, feasibility, and efficacy of the extraperitoneal tissue retraction technique in extraperitoneal pure sp-RARP with the da Vinci Si surgical system. Methods Data from 42 patients were analyzed retrospectively from December 2018 to February 2020. The extraperitoneal tissue retraction technique was not used in 20 patients (group I) and was used in 22 patients (group II). Preoperative, intraoperative, and postoperative data were collected. The oncological and functional data during late follow-up were recorded. Results All patients successfully underwent extraperitoneal pure sp-RARP. No patients required conversion to a multiport surgery or placement of additional assistant ports. The two groups were similar regarding baseline features. The median operation time in group I was significantly longer than that in group II (P < 0.001). The estimated blood loss volume in group I was significantly higher than that in group II (P < 0.001). There were no serious complications in either group. There were four cases of peritoneal tears in group I and none in group II (P = 0.043). The surgical margin and lymph nodes were negative in both groups. The oncological and functional outcomes were similar between the two groups 6 months after the procedure. Conclusions The extraperitoneal tissue retraction technique is safe and feasible. The technique promotes tissue exposure and expands the surgical working space, which is important for achieving extraperitoneal pure sp-RARP with the da Vinci Si surgical system, especially for beginners. The short-term oncological and functional outcomes were within acceptable ranges. The long-term effects of this technique need further evaluation.